Determinants of stakeholders' attitudes and intentions toward supporting the use of Wolbachia-infected Aedes mosquitoes for dengue control - Ahmad Firdhaus Arham; Latifah Amin; Muhammad Adzran Che Mustapa; Zurina Mahadi; Mashitoh Yaacob; Maznah Ibrahim (BMC, 2021)
Abstract Background A recent approach in controlling dengue is by using the Wolbachia-infected Aedes mosquito (WiAM). The approach has been reported to be more effective than traditional methods, such as fogging. Therefore, it is imperative to assess the factors predicting its acceptance among stakeholders before implementing this technology more widely in Malaysia. Methods The survey data were collected from two primary stakeholder groups using a stratified random sampling technique. The two primary stakeholder groups were scientists (n = 202) and the public (n = 197) in the Klang Valley region of Malaysia, a hot spot area known for the high rate of dengue cases. The respondents answered questions on a seven-point Likert scale survey regarding trust in key players, attitudes toward nature versus materialism, religiosity, perceived benefits, perceived risks, attitudes, and intentions. The data were analyzed using Smart Partial Least Square (SmartPLS) software (version 3.2.6) to determine the predictors influencing attitudes and intentions to support the use of WiAM technology. Results The results indicated a strong positive relationship between attitudes and intentions to support the use of WiAM (β = 0.676, p < 0.001). The most important significant predictor for attitudes was perceived benefits (β = 0.493, p < 0.001), followed by perceived risks (β = − 0.080, p = 0.048). Trust in key players, attitudes toward nature versus material, and religiosity had indirect relationships with attitudes through the perceived benefits and risks. Conclusions The identified predictors can serve as indicators for the decision-making process regarding WiAM implementation in Malaysia and other developing countries with similar demographics and cultures.